KARAKTERISTIK PENGGUNAAN ABU SERBUK KAYU SEBAGAI SUBTITUSI FILLER PADA CAMPURAN LASTON LAPIS AUS - Cut Yuslinggan Cahya; Sofyan M. Saleh; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2018)
Most of the filler material is a natural product such as rock ashes that increasingly limited and possesses high economic value. The further innovations in filler substitute by using alternative materials are demanded such as waste saw dust to become economical and unlimited resources. This study aims to determine the effect of the use of sawdust and Portland cement as a filler over AC-WC aggregate mixture characteristics. Further, sawdust and the Portland cement includes as the substitution. The filler substitution sawdust and Portland cement respectively amounted to 75% ASK - 25% SP, 50% ASK - 50% SP, 25% ASK - 75% SP and 0% ASK - 100% SP. Moreover, the experiment produced Substitution of 6.1% KAO for 75% sawdust - 25% Portland cement, Substitution of 6% for 50% sawdust - 50% Portland cement, Substitution of 5.85% for 25% sawdust - 75 % Portland cement and Substitution of 5.31% for 0% sawdust - 100% Portland cement. The best resulted KAO found in 0% sawdust substitution and 100% portland cement with 5.31%. The high-grade stability value with 30 minutes of regular water immersion is 1300,38 kg within 0% ash of sawdust substitution and 100% of Portland cement. The lowest stability value with 30 minutes of regular water immersion is 1056.09 kg within 75% sawdust substitution and 25% of Portland cement. The sawdust and portland cement durability value accomplished the Bina Marga 2014 specification (≥ 90%). The ANOVA test proved the addition of sawdust and portland cement in the asphalt mixture affects the stability value of the regular water immersion.